2023
DOI: 10.3390/life13051125
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Electrical Stimulation for Associative Memory Enhancement: State-of-the-Art from Basic to Clinical Research

Abstract: Associative memory (AM) is the ability to bind new information into complex memory representations. Noninvasive brain stimulation (NIBS), especially transcranial electric stimulation (tES), has gained increased interest in research of associative memory (AM) and its impairments. To provide an overview of the current state of knowledge, we conducted a systematic review following PRISMA guidelines covering basic and clinical research. Out of 374 identified records, 41 studies were analyzed—twenty-nine in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
(318 reference statements)
2
2
1
Order By: Relevance
“…reaction time, correct rejection, false memories) 35,36 and one study even reported inhibitory effects 52 . This is in contrast with the results of the standard tES studies which generally tend to favor PPC as the cortical region where stimulation provides beneficial effects on AM 51 . Taken together, these data could imply that, although spatial optimization is certainly a relevant factor, it might not be sufficient to lead to strong AM facilitation.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…reaction time, correct rejection, false memories) 35,36 and one study even reported inhibitory effects 52 . This is in contrast with the results of the standard tES studies which generally tend to favor PPC as the cortical region where stimulation provides beneficial effects on AM 51 . Taken together, these data could imply that, although spatial optimization is certainly a relevant factor, it might not be sufficient to lead to strong AM facilitation.…”
Section: Discussioncontrasting
confidence: 95%
“…Stimulating prefrontal cortex (PFC) 34,50 repeatedly failed to produce facilitatory effects. This is in line with the results of the previous research regarding standard tES montages which do not support PFC as an optimal cortical target in associative memory studies (reviewed in 51 ). On the other hand, HD studies stimulating parietal regions yielded variable results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The optimal number of sessions and the time period between them remain to be established in future studies. In healthy people, experiments showed that the effect of a single session of stimulation can be observed after a day; meanwhile, after that period, the aftereffects are negligible [68].…”
Section: Effects On Spatial Navigationmentioning
confidence: 99%